(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
Octylphenol polyethoxylates (OPEs) constitute a class of non-ionic surfactants extensively3employed in various industrial applications. However, concerns have arisen regarding the potential environmental and human health impacts of OPEs because of their widespread use and persistence in aquatic environments. Bioremediation of OPE in the environment using OPE-degrading bacterium is appealing as bacterial metabolism converts OPE to harmless carbon dioxide and water as byproducts. In this study, various secondary growth models such as Luong, Yano, Teissier-Edward, Aiba, Haldane, Monod, Han, and Levenspiel were employed to model the inhibitory effect of high OPE concentrations to the growth rate of Aeromonas sp. TXBc10 the bacterium on OPE. Following thorough statistical analyses such as root-mean-square error (RMSE), adjusted coefficient of determination (adjR2), bias factor (BF), and accuracy factor (AF), the Teissier model emerged as the most optimal choice. All of the studied models showed good fittings except Moser, Monod and Hinshelwood which showed the poorest curve fitting. The calculated value for the Luong’s constants maximal degradation rate, half saturation constant for maximal degradation, maximal concentration of substrate tolerated and curve parameter that defines the steepness of the growth rate decline from the maximum rate symbolized by qmax, Ks, Sm, and n were 8.91 h-1 (95% confidence interval or C.I. from 7.15 to 10.67), 1116.19 mg/L (95% C.I. from 815.53 to 1416.84), 1074.6 mg/L (95% C.I. from 1037.8 to 1111.5) and 11.90 (95% C.I. from 5.30 to 18.51), respectively. It is possible that these new constants found when modeling could be useful inputs for future modeling efforts. In addition incorporating substrate inhibition kinetics into risk assessment models contributes to a more accurate evaluation of the potential risks associated with the presence of toxic substrates in contaminated sites. This information is vital for decision-making in environmental management.